Development of bio-health products from rice bran ferulates - Bagalkotkar, Gururaj; Ismail, Maznah; Ho, K. L.; R., Nur Hazwani (Sarawak Biodiversity Centre, 2008)
Rice bran, the major byproduct of the rice milling industry is also the source of high quality vegetable oil viz. rice bran oil (RBO). Rice bran oil has attracted much medical attention due to its strong hypocholesterolemic properties primarily attributable to its balanced fatty acid composition and high levels of antioxidant phytochemicals such as oryzanols, tocopherols and tocotrienols. Rice bran and rice bran oil have particularly been under investigation recently because of their potential benefits. Rice bran oil is also rich source of phytochemicals with nutraceutical and antioxidant properties and product development could certainly add value to these bio-resources that are available in abundance. Nevertheless, there is yet a study on the biological properties and identification of stabilized rice bran phytochemical rich fractions and biotransformation products from rice bran oil. The phytochemical rich fractions from RBO were successfully extracted using SFE and sequential extraction methods. Ferulate esters were isolated and purified using R-HPLC and Prep-HPLC and analyzed using LC-MS (Q-TOF). Antioxidant activity of ferulate rich fractions from RBO has been determined using DPPH method and anticancer activity of ferulate derivatives from RBO has been determined using MTS assay against HT-29 cancer cell lines. The extracted ferulic acid and its derivatives (campesteryl ferulate (1) and sitosterol ferulate (2)) were tested against human colon cancer (HT-29) cell line using MTS cytotoxic assay. Ferulic acid derivatives (campesteryl ferulate (1) and sitosterol ferulate (2)) exhibited significant cytotoxic activity against the tested cancer cell line with the IC50 values of 420 and 465 μg/ml, respectively. These enriched fractions and phtytochemicals from rice bran could find application as antitumour agents and natural antioxidants for processed foods or as dietary supplements.